Are Italian nurses ready for patient blood management program? A national social media survey - Barchielli, Chiara; Landriscina, Sara; Castelluzzo , Sabrina Claudia; Alaimo , Marco (Acta Biomedica Atenei Parmensis, 2023)
Background and aim: Blood transfusion is one of the five most overused procedures in healthcare. Patient Blood Management (PBM) is a multimodal and multidisciplinary strategy that aims to properly manage the patient blood. In 2015 the Italian National Blood Centre explicitly mentioned the need for the identification of dedicated nursing staff to implement this approach. The purpose of this study is to investigate if Italian nurses are prepared and willing to implement the PBM. Methods: We conducted a social media survey that registered 235 respondents from the whole Italian territory over a one-month period (15th of May-15th of June 2020). The 23 open and closed-ended questions were intended to investigate the views, the inclinations, and intentions of healthcare professionals towards PBM. Results: PBM can still be considered as a niche topic. Therefore, most respondents declared themselves willing to know more about it, to acquire new skills and grow professionally, to determine benefits for the hospital, to improve the quality of nursing care and act evidence based, and to enhance the nursing role in the multidisciplinary team. Conclusions: PBM programs are conducted and implemented effectively worldwide, and Italian nurses recognize its importance and are willing to implement it and be a part of it for what then bedside care, the educational, and the managerial role are concerned. (www.actabiomedica.it) Key words: Patient blood management, blood transfusion, bloodless nurse, bloodless coordinator, nursing education, nursing management.